Correlation of caecal intubation rate to volume: colonoscopists should undertake at least 120 procedures per year. Issue 3 (17th December 2013) - Verma, Ajay M; Dixon, Andrew D; Chilton, Andrew P
Abstract : Introduction: The measurement of the quality of colonoscopy has been in the vanguard of quality improvement. The Joint Advisory Group on Gastrointestinal endoscopy (JAG) has issued guidance for practitioners to achieve caecal intubation rates (CIR) of ≥90% and to undertake ≥100 colonoscopies per annum. The British Society of Gastroenterology National Colonoscopy Audit published in 2012–2013 demonstrated a combined CIR of 92.3%. In 2012, we published data from 16 064 colonoscopies showing a combined CIR of 90.57%—both meeting JAG's standard. Analysis of our audit looked at the relationship of volume and outcome. CIR of operators performing ≥100 procedures per annum was 91.76%; those performing <100 was 87.77%. The 2-year data we collected involved 120+ operators. This provided an opportunity to study the correlation between volume and CIR in detail. Methods: We analysed 129 operator records who had undertaken 20–399 procedures per annum (total 12 594). Each operator's volume was plotted against CIR as individuals and groups of operators undertaking a similar annual volume. 9859 procedures (78.3%) were performed by operators undertaking 20–199 procedures per annum (120 operators); this subgroup was further analysed. Results: When plotting individuals and groups of individuals who have undertaken a similar annual volume against CIR, the trend-lines cross a 90% CIR at a volume of 120–125 procedures. The subgroup analysis showed the trend-line crossing at 110–120 procedures. Conclusions: This detailed analysis of 12 594 colonoscopies over 2 years suggests that JAG should advise operators to undertake ≥120 procedures per annum to support the quality standard for CIR of ≥90%.